The Effect of Non-Performing Financing and Financing to Deposit Ratio on Return on Assets at BJB Syariah (2019-2024) - Wahyudin, Dafiq; Azizah, Wuri (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – This study aims to analyze the effect of Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on Return on Assets (ROA) at BJB Syariah for the period 2019-2024. Previous research has yielded inconsistent results, necessitating further investigation in regional Islamic banking contexts to understand the effectiveness of financing better. Design/Methods/Approach – The study utilizes secondary data from quarterly financial reports, which are analyzed using multiple linear regression with EViews 13. Classical assumption tests, including normality, autocorrelation, heteroscedasticity, and multicollinearity, were conducted to ensure model validity. Findings – NPF has a negative but insignificant effect on ROA (coefficient = -0.149986; p-value = 0.1713), meaning changes in Non-Performing Financing do not significant impact on profitability. Conversely, FDR has a negative and significant effect on ROA (coefficient = -0.039732; p-value = 0.0008), indicating that increased third-party fund distribution has not been fully effective in enhancing bank profit. Simultaneously, NPF and FDR have a significantly affect ROA with an R-squared of 0.48, explaining 48% of ROA variation. Research Implications/Limitations – The study’s limitation lies in the R-squared value, indicating that 52% of ROA variation is influenced by external factors such as BOPO, CAR, NIM, and Macroeconomic conditions. The limited period (2019-2024) and focus on one Islamic bank require caution in generalizing results. Originality/Value – This study provides empirical contributions regarding the effectiveness of financing and risk management in regional Islamic banks, highlighting the importance of the quality of fund distribution rather than quantity in improving profitability.